Transition Pathways toward Agroecology in Semi-arid “Crop-Livestock” Systems at Rhahla, Gaafour - Ouerghemmi, Hassen; Alary, Veronique; Shiri, Zahra; Dhraief, Mohamed Zied; Oueslati-Zlaoui, Meriem; Majri, Rihab; Rudiger, Udo; Frija, Aymen; Idoudi, Zied; Souissi, Asma; Dhehibi, Boubaker; Mannai, Amal; et al. (International Center for Agricultural Research in the Dry Areas, 2023)
Specialization and intensification of agricultural systems and the search for profit have guided the evolution of agriculture to new farming models emerging to respond to a growing demand for food, despite the complementary relationships between crops and livestock farming activities which have been documented in many studies. This trend has increased the vulnerability of farms to shocks, decrease land productivity and impair water use efficiency. One of the major production systems in El Kef-Siliana transect is the tree-crop-livestock system which is nowadays characterized by many problems related to weak integration, low productivity and incomes and lack of inputs (especially fodder), etc. As a response to these challenges the new paradigm of sustainable production intensification as a part of an agroecological transition process, recognizes the need for a productive and remunerative agriculture which at the same time conserves and enhances natural resources and positively contributes to harnessing the environmental services. El Rhahla as a part of ALL is a typical zone where crop-livestock system is dominated, by a big herd of sheep raised on small olive groves. The same difficulties were always there in terms of productivity, profitability, and integration. Based on many observations and refereeing to some consultations with local actors and community, many bottlenecks were defined for this dominant production system, aiming to co-define a promoting transition pathway which can be reflected on field by actions. The used participatory approach was an exercise of “Visioning”, a focus group discussion conducted with the community of El Rhahla. This approach points to reflect the perception of farmers for a better desirable future for their activities as well as their community. The desires were then discussed and mapped referring to agroecology principles. The AE transition pathway identified in crop-livestock system in Rhahla suggests an emphasis on the diversification and the integration of the farm activities through improving forage availability and animal value chain reinforcement. The resulting impact pathway promotes improving soil health, increasing economic autonomy at farm and national level and scaling AE transition through sectorial and inter sectorial policies. A mass of actions will be implemented during 2023 and 2024 to ensure a possible transition in the intervention area and to get lessons from it to all of the Tunisia crop-livestock system.